The Risk/Return Tradeoff in Relation to Corporate Performance within Chinese Companies - Fu, Xihao (2015)
The world’s 2nd largest economy, China, has been attracting global attention for decades. With the fast – growing market and increasing challenges Chinese companies confront with, what kinds of approaches could be adopted to generate income and simultaneously maintain the growth of individual firms and domestic and global market shares? This paper is intended examine the risk/ return tradeoffs under different circumstances to find out the patterns of differences from firm to firm. Specifically, profit risk – return relationship and cash flow risk – return relationship are compared with each other to explore corporate decision making on risky actions. Further, comparing risk preferences of high and low performers, which correspond to gains and losses in prospect theory, offers a clear image of those patterns. It is found that corporate risky actions involving volatile income could have a negative impact on the return at the period, while those actions engaging in potential illiquidity play a positive role in improving corporate performance. On the other hand, the results of tests for high and low performers comply with the prediction of prospect theory, positive link in high performers and negative association in low performers. This may be of interest to firms confused about risk/ return tradeoffs, encouraging them to better understand the situation and make achievements without taking so much risk.